Mechanism of the Aminolysis of Fischer Alkoxy and Thiocarbene Complexes: A DFT Study - Andrada, Diego Marcelo (2010)
B3LYP calculations have been carried out to study the reaction mechanism of the aminolysis of Fischer carbene complexes of the type (CO)5Cr═C(XMe)R (X = O and S; R = Me and Ph). We have explored different possible reaction mechanisms either through neutral or zwitterionic intermediates as well as a general base catalysis assisted by an ammonia molecule. Our results show that the most favorable pathway for the aminolysis of Fischer carbene complexes is through a stepwise reaction via a zwitterionic intermediate generated by the initial nucleophilic attack. We have found that the ammonia-catalyzed mechanism entails a significantly lower barrier for the rate-determining step than the uncatalyzed one. At lower pressure gas-phase conditions, the rate-determining step corresponds to the concerted proton transfer and MeXH elimination. Thiocarbene complexes show a higher energy barrier for this rate-determining step due to the lower basicity of the MeS− substituent. At higher pressure or in solution, the rate-determining step corresponds to the initial nucleophilic attack. Our results indicate that the transition state of the nucleophilic attack is more advanced and has a higher barrier for alkoxycarbene than thiocarbene complexes due to the stronger π-donor character of the alkoxy group that reduces the electrophilicity of the attacked carbene atom making the nucleophilic attack more difficult.